Analysis of Factors Influencing the Implementation of China’s Belt and Road Initiative Projects in Sri Lanka - Muhammad Dimas Audi Nurapraja (Eduvest - Journal of Universal Studies, 2026)
The Belt and Road Initiative (BRI) is China’s foreign policy program launched by President Xi Jinping in 2013. Sri Lanka has become one of the significant BRI partner countries due to its strategic location, particularly the Colombo Port and the Hambantota region, which are important points along international maritime trade routes. This research aims to analyze the factors influencing the implementation of China’s BRI program in Sri Lanka and examine its implications for Sri Lanka’s national development. The study employs a qualitative approach using secondary data analysis through library research. The theoretical framework applied in this research is dependency theory. The findings reveal two interrelated dimensions of interests: (1) China’s interests in Sri Lanka, including transportation infrastructure development, energy cooperation, and soft power projection; and (2) Sri Lanka’s interests in China, including foreign direct investment, infrastructure development, connectivity enhancement, and technology transfer. The implementation of the BRI in Sri Lanka demonstrates the relevance of dependency theory in explaining the dynamics of bilateral relations between developed and developing countries in the contemporary era.